PENGARUH PEMBERIAN EDUKASI BASIC LIFE SUPPORT (BLS) PADA KADER POSYANDU DALAM MENGHADAPI BENCANA DI WILAYAH KERJA PUSKESMAS PANGKAL BALAM KOTA PANGKALPINANG TAHUN 2022 - Hasan, Abdul Kadir (NHM PRESS, 2023)
Natural disaster is a natural phenomenon that occurs directly or indirectly disrupts human life. In this case, natural disasters can cause losses to humans both materially, non-materially and even souls. The purpose of this study was to increase the knowledge, skills and preparedness of posyandu cadres regarding basic life support (BHD). The research design used the Quasi Experiment Design method and the One Group Pretest-Posttest Design, with 1 treatment group. The number of respondents in this study were 30 people. This research was conducted at the Pangkal Balam Health Center, Pangkal Balam District, Pangkapinang City. The time for the research was conducted in October 2022. The subjects of this study were health cadres at the Pangkal Balam Health Center with work experience that was adjusted to predetermined criteria. Research data were analyzed using paired t test. Based on the statistical test results, the researcher obtained several results, namely the correlation value that was carried out by respondents between the 2 variables (Pre and Post) which had a value of 0.428, meaning that the relationship was sufficient and positive. Continuing measurement of results Probability value/p value of Paired T test: Result = 0.123. Meaning: There is no difference between before and after treatment. Reason: The p value > 0.05 (95% confidence). So it can be concluded that there is no difference before and after the implementation of the respondents to the research on the effect of providing basic life support (BLS) education to posyandu cadres in dealing with disasters in the work area of the Pangkal Balam Puskesmas, Pangkal Pinang City in 2022. It is hoped that it can increase the provision of information and education to increase knowledge and skills in basic life support (BHD) and the creation of a Disaster Response Posyandu considering the geographical location of the Pangkal Balam Health Center in the Port area of Palembang City